DESIGN AND TECHNICAL REQUIREMENTS FOR UAV SYSTEMS IN 3D TERRAIN MAPPING (American Journal of Technology and Applied Sciences, 2022)
This article summarizes the current technical requirements and architectural solutions for unmanned aerial vehicles (UAVs, drones) intended for three-dimensional terrain mapping (photogrammetry, LiDAR, visual-optical SLAM systems). Recommendations are provided regarding platform selection, sensors (cameras, LiDAR, IMU, GNSS/RTK/PPK), survey parameters (GSD, overlaps, trajectories), data processing (SfM–MVS, LiDAR pipelines, visual-inertial filters), and accuracy assessment.